Congestion control in Mobile Ad-Hoc networks (MANETs) - Alam, Md. Mahbubul; Shetu, Tanmoon Taz (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2011.